15 million Euro invested for mitigation action in Thailand's rice sector - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The NAMA Facility has approved the EUR 14,900,000 Thai Rice NAMA project. Implementing the project is the consortium of Thai Rice Department (TRD), GIZ, IRRI, SRP, and other rice-based public/private partners. The project builds on IRRI/CCAFS science on 4 different low-emission development technologies and targets to reach 100,000 rice farmers in 6 provinces. The expected 21.5mio Euro additional direct financial investments from the private sector and 9mio Euro in kind contribution from TRD leverage fund requirement towards better project implementation.